Model Fair Use/Fair Dealing Hak Cipta Atas Buku dalam Pengembangan IPTEK pada Pendidikan Tinggi - Anis Mashdurohatun; M. Ali Mansyur (Jurnal Hukum IUS QUIA IUSTUM, 2017)
This research is to study: first, how is the model of fair use/fair dealing of Copy Right of Book in the development of Science and Technology in higher institution based upon the moral right, economic and social rights? Second, what things are deemed important as the base in measuring the use of book properly and equitably for many parties? This research was conducted using the juridical sociological approach. The result of the research showed that first, the model of fair use/fair dealing of Copy Right in developing the Science and Technology in Higher Institution based upon the aspects of moral right, economic right, and social right that is by balancing the elements of fair use/fair dealing towards the creator in State Higher Institutions and Private Higher Institutions, Publisher/IKAPI/YRCI/LMK, Book Store/Cooperation, Institute for Research and Community Service, Library Institute, Researchers/Lecturers/Students for creating the accessible, affordable and qualified books.  Second, the existence of MoU/cooperation between the Institute of Higher Education and the publishers/YRCI/ Collective Management Organization and Photocopies Entrepreneur through a licensing agreement by paying amount of money for royalties, the realization of book circulation which is comparable with the creation of decent appreciation to Writer.